The Impact of Charismatic Leadership on Organizational Culture - Chiman Ahmed Hamad Ameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The present study examines the complex relationship between charismatic leadership qualities and organizational culture, with a specific focus on private enterprises operating in the Erbil-Kurdistan region of Iraq. The objective of our research is to investigate the impact of charismatic leadership on organizational culture. Charismatic leadership is characterized by qualities such as visionary thinking, confidence, a risk-taking tendency, and flexibility. We aim to understand how these traits collectively shape and influence the broader organizational culture. The study utilized various quantitative approaches, such as correlation analysis and multiple regression, to examine the connections between charismatic leadership attributes and organizational culture. The research sample consists of 89 participants selected from various private firms located in Erbil. The results obtained from this study highlight the importance of charismatic leadership in influencing the development and characteristics of organizational culture. The emergence of each charismatic feature has been proven to be statistically significant and positively predictive of organizational culture. This highlights the tremendous influence that leaders may have in shaping an organization's values, norms, and practices. The results of the multiple regression analysis confirmed these links and showed that charismatic leadership traits explain a lot of the differences in organizational culture.